La Gestión del Tiempo en la Sala de Clases y Los Rendimientos Escolares en Escuelas Con Jornada Completa en Chile - Villalta-Paucar, M (Universidad Nacional Autonoma de Mexico, 2015)
This article analyzes the use of time in the classroom by teachers in full-day school (FDS) establishments, based on subject matter, administration of the establishment, and performance on the Educational Quality Assessment System (Spanish acronym SIMCE) test. The design of the study is descriptive-analytic and videos are analyzed from three consecutive lessons with 13 teachers of Mathematics and Basic Level Language in public and private establishments. We observe that teachers in establishments with more than 8 years in FDS programs and high SIMCE scores give more procedural instructions, present instructional content more frequently in class, and spend less time disciplining students. It is show that years implementing FDS programs have a positive effect on class organization and on time spent on content and instructional tasks. © 2015. All Rights Reserved.